Thomas Brett's Puritan Papers: a Lost Collection of Elizabethan Manuscripts - Thompson, W. D. J. Cargill (The journal of ecclesiastical history, 1976)
Among the sources that Strype used for his Life of Whitgift was a group of MSS., relating to the activities of the Puritans between c. 1588 and 1591, which he was lent in 1711 by the Rev. Thomas Brett, LL.D., of Spring Grove, Kent, the future Non-Juror bishop. The papers had originally belonged to a maternal ancestor of Brett's, Sir John Boys of St. Gregory's, Canterbury, a successful Elizabethan lawyer who had been M.P. successively for Sandwich, Midhurst and Canterbury, and Recorder of Canterbury and Sandwich, and who had held the office of steward of the Liberty of the see of Canterbury for almost forty years under archbishops Parker, Grindal, Whitgift, Bancroft and Abbot. Sir John Boys left no direct issue, but numerous collateral relations and the papers appear to have descended through the family of his nephew Edward Boys, who inherited the manor of Betshanger from his uncle, until the beginning of the eighteenth century when they came into Brett's possession after the death of his mother's brother, Jeffray Boys of Betshanger, in 1703.